Contralateral Occlusion Increases the Risk of Neurological Complications Associated with Carotid Endarterectomy - Laura Capoccia; Enrico Sbarigia; Anna Rita Rizzo; Chiara Pranteda; Danilo Menna; Pasqualino Sirignano; Wassim Mansour; Andrea Esposito; Francesco Speziale (International Journal of Vascular Medicine)
Objective. To report on the incidence and factors associated with the development of perioperative neurological complications following CEA in patients affected by carotid stenosis with contralateral occlusion (CO) and to compare results between those patients and the whole group of patients submitted to CEA at our vascular division from 1997 to 2012. Methods. Our nonrandomized prospective experience including 1639 patients consecutively submitted to CEA was retrospectively reviewed. 136 patients presented a CO contralateral to the treated carotid stenosis. Outcomes considered for analysis were perioperative neurological death rates, major and minor stroke rates, and a combined endpoint of all neurological complications. Results. CO patients more frequently were male, smokers, younger, and symptomatic (P < 0.001), presented with a preoperative brain infarct and associated peripheral arterial disease (P < 0.0001), and presented with higher perioperative major stroke rate than patients without CO (4.4% versus 1.2%, resp., P = 0.009). Factors associated with the highest neurological risk in CO patients were age >74 years and preoperative brain infarct (P = 0.03). The combination of the abovementioned factors significantly increased complication rates in CO patients submitted to CEA. Conclusions. In our experience CO patients were at high risk for postoperative neurological complications particularly when presenting association of advanced age and preoperative brain infarction.